2015
DOI: 10.1063/1.4916084
|View full text |Cite
|
Sign up to set email alerts
|

Optical-phonon-mediated photocurrent in terahertz quantum-well photodetectors

Abstract: Articles you may be interested inSpace charge mediated negative differential resistance in terahertz quantum well detectors J. Appl. Phys. 110, 013714 (2011); 10.1063/1.3605480 Two-photon-absorption-induced nonlinear photoresponse in Ga As ∕ Al Ga As quantum-well infrared photodetectors Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The material of the device [3] was grown by molecular beam epitaxy (MBE) technique. These layers consist of (starting from the semi-insulating GaAs substrate) [9], a 400 nm GaAs bottom contact layer, 30 periods of 15.5 nm GaAs/70.2 nm Al 0.03 Ga 0.97 As and an 800 nm GaAs top contact layer. Both the contacts are silicon doped at 1×10 17 cm −3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material of the device [3] was grown by molecular beam epitaxy (MBE) technique. These layers consist of (starting from the semi-insulating GaAs substrate) [9], a 400 nm GaAs bottom contact layer, 30 periods of 15.5 nm GaAs/70.2 nm Al 0.03 Ga 0.97 As and an 800 nm GaAs top contact layer. Both the contacts are silicon doped at 1×10 17 cm −3 .…”
Section: Methodsmentioning
confidence: 99%
“…The solid-state THz quantum-well photodetectors (QWPs) [5] based on low dimensional semiconductor structures have many advantages of fast response, mature manufacturing process and small volume, which are suitable for constructing THz high-speed communication and fast imaging systems. For these devices, the principle of operation that based on quantum-well sub-band transitions [6][7][8] cannot directly absorb normal incident light, so a 45°-incident coupling scheme or an integrated coupler [9] such as metal gratings [10,11], etched gratings [12,13] are commonly used to excite the localized electrons in quantum wells from the ground sub-band into the higher subbands. THz QWPs with fixed periodic grating couplers, such as one-dimensional (1D) metal gratings, two-dimensional (2D) metal gratings and dielectric gratings have been studied in previous works.…”
Section: Introductionmentioning
confidence: 99%
“…There is a great difference at about 9.0 THz between the two devices. For the C-QWIP, there is only a response peak (8.94 THz) that is introduced by the polarization field of LO phonon [36,37]. However, for the G-QWIP, there are two response peaks at 8.84 THz and 8.98 THz.…”
Section: Device Design Fabrication and Characteristicsmentioning
confidence: 99%
“…It has been demonstrated that the terahertz waves are manipulated by using the electrical control [5] or optical illumination. [6,7] Based on these studies, here, we report a ferroelectrically controlled device to realize a tunable modulation controlling the propagation properties of the terahertz waves. The resonance response characteristics of graphene metamaterials could be dynamically tuned in this device due to the influence of ferroelectricity from the Si:HfO 2 layer.…”
Section: Introductionmentioning
confidence: 99%